Birdscapes : birds in our imagination and experience - Mynott, Jeremy (Princeton University Press, 2009)
What draws us to the beauty of a peacock, the flight of an eagle, or the song of a nightingale? Why are birds so significant in our lives and our sense of the world? And what do our ways of thinking about and experiencing birds tell us about ourselves? Birdscapes is a unique meditation on the variety of human responses to birds, from antiquity to today, and from casual observers to the globe-trotting "twitchers" who sometimes risk life, limb, and marriages simply to add new species to their "life lists."